PENGARUH DELIVERY SPEED, VIRAL MARKETING DAN SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN MELALUI KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA NABILA BUAH DI SITUBONDO - Raniah, Dinta Carissa; Pramitasari, Triska Dewi; Tulhusnah, Lusiana (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of the study was to determine the Effect of Delivery Speed, Viral Marketing and Service Quality on Purchasing Decisions Through Consumer Trust as an Intervening Variable at Nabila Buah in Situbondo. The sampling technique used in this study was simple random sampling of 97 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM. The results of the study showed that Delivery speed had a positive and significant effect on Consumer Trust, Viral marketing had a positive and significant effect on Consumer Trust, Service quality had a positive and significant effect on Consumer Trust, Delivery speed had a negative but significant effect on Purchasing Decisions, Viral marketing had a positive and significant effect on Purchasing Decisions, Service quality had a positive but not significant effect on Consumer Trust, Consumer Trust had a positive and significant effect on Purchasing Decisions, Delivery speed had a positive and significant effect on Purchasing Decisions through Consumer Trust, Viral marketing had a positive and significant effect on Purchasing Decisions through Consumer Trust, Service quality had a positive but not significant effect on Purchase decision through Consumer Trust.